2015
DOI: 10.1002/chem.201500843
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Base on Pd@MIL‐101‐NH2(Cr) as Catalyst for the Suzuki–Miyaura Cross‐Coupling Reaction

Abstract: The chemical stability of metal-organic frameworks (MOFs) is a major factor preventing their use in industrial processes. Herein, it is shown that judicious choice of the base for the Suzuki-Miyaura cross-coupling reaction can avoid decomposition of the MOF catalyst Pd@MIL-101-NH2 (Cr). Four bases were compared for the reaction: K2 CO3 , KF, Cs2 CO3 and CsF. The carbonates were the most active and achieved excellent yields in shorter reaction times than the fluorides. However, powder XRD and N2 sorption measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 88 publications
3
30
0
Order By: Relevance
“…The experiments were carried out at 4 mmol scale. Interestingly, the XRPD pattern of the recovered material revealed that the framework did not decompose after five reaction runs (Figure a), despite the previously reported detrimental effect of carbonates on its mesoporous polymorph MIL‐101‐NH 2 . Slight changes were observed in the 2Θ value and relative intensities of the main diffraction peaks; this has been reported previously for this MOF, and ascribed to its flexible nature .…”
Section: Resultssupporting
confidence: 60%
“…The experiments were carried out at 4 mmol scale. Interestingly, the XRPD pattern of the recovered material revealed that the framework did not decompose after five reaction runs (Figure a), despite the previously reported detrimental effect of carbonates on its mesoporous polymorph MIL‐101‐NH 2 . Slight changes were observed in the 2Θ value and relative intensities of the main diffraction peaks; this has been reported previously for this MOF, and ascribed to its flexible nature .…”
Section: Resultssupporting
confidence: 60%
“…When Pd 0 ‐MIL‐101‐NH 2 (Cr) was used, the addition of K 2 CO 3 (0.1 equiv) was detrimental for the selectivity (Table , entries 1–3 vs. Table , entries 3–5). However, these results are consistent with our and others′ recent investigations on the stability of the MIL‐101(Cr) framework in basic media. The presence of K 2 CO 3 leads to a degradation of the porous framework, which can no longer prevent the agglomeration of Pd nanoparticles.…”
Section: Resultssupporting
confidence: 94%
“…S12, ESI †). This agrees with our previous findings on the effect of the base on the MOF's structure, 16 and demonstrates the advantage of immobilising bifunctional catalysts. On a larger scale experiment and under otherwise identical conditions as those used in Table 2, entry 5, UiO-68-2CH 3 -L-PSE afforded 99% conversion in the absence of base and could be recycled three times without any loss in catalytic activity (Table S5, ESI †).…”
supporting
confidence: 93%
“…15b This bifunctional catalyst is therefore an ideal candidate for immobilisation in a MOF because it avoids the use of base additives that can be detrimental to the MOF structure. 16 We synthesised a new Ir-NHC metallolinker containing an alcohol donor group, H 2 L ( Fig. 1 and ESI † for full details), and introduced it into a zirconium MOF, UiO-68-2CH 3 (also known as PCN-56), 17 which is constructed from 2 0 ,5 0 -dimethylterphenyl-4,4 00 -dicarboxylate (dmtpdc) linkers and Zr clusters.…”
mentioning
confidence: 99%